An Obstructed Anomalous Left Anterior Descending Coronary Artery Arising from the Right Coronary Artery Requiring Surgical Intervention. (19th September 2016) - Mironov, Alexander; Galligan, Sean; Kakauridze, Aleksandre; Marmur, Jonathan D.
Abstract : A 47-year-old female presented to our hospital with symptoms of stable angina. Cardiac catheterization revealed a rare coronary artery anomaly of the left anterior descending (LAD) artery branching off the right coronary artery ostium. Furthermore, the anomalous LAD artery exhibited significant atherosclerotic obstruction. Our review of the literature found only nine such previously described cases. Due to the unique nature of coronary artery anomalies and their complications, we would like to contribute our case to the medical literature.